2020
DOI: 10.3122/jabfm.2020.01.190120
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Decision-Making for Antidepressants and Educational Level

Abstract: Background: Despite recommendations to screen adults for depression in primary care, little is known about how people across education levels decide to treat their depression and factors that influence their decision. Methods: We conducted a secondary analysis of a national, probability-based web survey in Englishspeaking adults aged 40 or older living in the United States who reported they discussed starting or continuing an antidepressant with their clinician in the past 2 years. Respondents answered questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Effective shared decision making requires asking patients what they prefer. The SDM Process scores were fairly low compared to other conditions [ 12 , 20 ], but were similar to previously published SDM Process scores for depression treatment [ 13 ]. The patient responses on the individual items in the SDM Process scale revealed that 265 (80.8%) discussed options, 66 (20.1%) discussed pros (a lot or some), 28 (8.5%) discussed cons (a lot or some), and 228 (69.5%) were asked their preference; this is similar to how treatment decisions are discussed and framed [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Effective shared decision making requires asking patients what they prefer. The SDM Process scores were fairly low compared to other conditions [ 12 , 20 ], but were similar to previously published SDM Process scores for depression treatment [ 13 ]. The patient responses on the individual items in the SDM Process scale revealed that 265 (80.8%) discussed options, 66 (20.1%) discussed pros (a lot or some), 28 (8.5%) discussed cons (a lot or some), and 228 (69.5%) were asked their preference; this is similar to how treatment decisions are discussed and framed [ 12 ].…”
Section: Discussionsupporting
confidence: 85%
“…Also, patients who reported receiving the DA may have different knowledge than those who received and reviewed the DA. Whether or not patients received a DA, there is still a significant knowledge deficit for patients in the sample, which is similar to a national study that found patients had inadequate knowledge about depression treatment [ 13 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…4 Our results show that the education level of patients may influence their self-efficacy and preparedness for decisionmaking. Although a lower education level has been reported to be associated with lower scores of involvements in shared decision-making, 20 education level alone cannot reflect the patient's capacity to obtain, process, and understand basic health information and services, ie, health literacy. Routinely screening patients for health literacy has not been shown to improve outcomes and is not recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The team lead by Purkable 13 conducted an intervention to promote discussions of quality of life goals. The associations between education level, depression care, and shared decision making is explored in the article by Brodney et al 14…”
Section: Family Medicine Carementioning
confidence: 99%